(untitled) (Fiep Bulletin - online, 2014)
Technical - combinatorial sports are often linked to the use of music. The methodology concerning the construction of an exercise makes reference to two different approaches. If the first is based on the absolute freedom of composition, the second is based on the music choice where the fundamental idea of the choreography springs from. The aim of this work is to strengthen the statement that the personal choice of the music as far as one’s exercise is concerned can lead to an improvement of the results. The sample, made up of 50 athletes practicing rhythmic and artistic gymnastics at a competitive level, has been subdivided into two groups according to the age; group 1 aged between 6 and 11 years old, group 2 aged between 12 and 18 years old. A multiple choice questionnaire, made up of four sections, has been used. The results confirmed the initial hypothesis. The description of the data has been carried out through the univariate analysis of the single variables; the differences between the two groups of athletes have been obtained through Wilcoxon test (variance analysis). The results have pointed out, in particular for the most experienced group of gymnasts that, besides the awareness that the music choice may, in some ways, have a leading role for the interpretation of the music, the music culture represents the linking factor between the gymnasts and their trainer in the construction of the choreography.